Hybrid Work System Transformation and Its Impact on Employee Welfare and Company Productivity - Sumiati (Yayasan Pendidikan Belajar Berdikari, 2023)
In addition, innovative performance measurement approaches must be developed to accurately assess employee contributions in both remote and in-office settings. Comprehensive research is needed to address this gap and tailor solutions to the unique context of the Indonesian workplace. This study uses a quantitative approach to obtain comprehensive data on the impact of hybrid work systems on employee welfare and organizational productivity. The results of this study are: The Effect of Hybrid Work System on Employee Welfare, The Effect of Hybrid Work System on Company Productivity, The Effect of Employee Welfare on Company Productivity, Indirect Effect: Mediation by Employee Welfare, Moderation Role of Type of work